Achilles Tendon Rupture Repairs: A Case Series Reporting Clinical Outcomes of a Novel Technique - Caroline Williams MS; Christopher P. Miller MD, MHS; John Y. Kwon MD (Foot & Ankle Orthopaedics, 2020)
Category: Trauma; Ankle; Sports Introduction/Purpose: Achilles tendon rupture repair has undergone several changes in the last ten years, aiming to minimize complications while maximizing clinical and functional outcomes. Selecting a less invasive approach instead of traditional open incision has shown through various studies to generate excellent results and significantly reduce post-operative infections. Choice of patient positioning during operative repair has also shown to be of great impact, with prone positioning being associated with elevated surgical times and anesthetic requirements, thus secondary affecting clinical outcomes. Other complications associated with prone positioning include neuropraxia and increased risk of iatrogenic ophthalmologic insults as compared to the supine position. This case report evaluates clinical outcomes of patients following treatment of Achilles rupture with a novel Medial Mini- Open Supine Achilles Repair Technique. Methods: Patients were selected for case series inclusion after undergoing novel Medial Mini-Open Supine Achilles Repair Technique for acute achilles rupture. Retrospective medical record review for demographic, perioperative and functional data was completed for each patient, with means, range and standard deviations calculated when appropriate. Patients were then followed postoperatively to monitor recovery. At a final follow up visit scheduled no sooner than six months post operatively, outcomes were assessed with three separate Patient-Reported Outcomes Measurement Information System (PROMIS) surveys; Physical Function, Pain Interference and Depression. Two separate Foot and Ankle Ability Measure (FAAM) assessments, ADLs and Sport, were also completed. Patients were also assessed for physical pain/discomfort using the Visual Analog Scale (VAS). Results: Eighteen patients were included in this study; fifteen male, three female. Mean age was 37.5 years (+-12, range= 20-68). Mean duration of surgery was 31.0 minutes (+- 7.0). Follow up duration averaged 11.8 months (range 6.0-13.5). All patients completed three Patient-Reported Outcomes Measurement Information System (PROMIS) studies and two Foot and Ankle Ability Measure (FAAM) surveys. Mean score for the PROMIS Physical Function survey was 52.3 (+-11.5), for Pain Interference, mean= 50.0 (+-7.30), and for Depression, mean=39.5 (+- 6.96). FAAM Sport survey showed a mean=71.3 (+-29.4), with ADLs form responses showing a mean of 90.7 (+-12.7). All patients reported 0/10 pain on Visual Analog Scale (VAS), and overall satisfaction with their outcomes. Conclusion: In reviewing data collected thus far, the Medial Mini-Open Supine Achilles Repair technique shows promise to serve as a viable option for achilles tendon rupture repair; ease of patient positioning preoperatively translates to decreased set up, operative, and sedation time, directly benefiting patients. No complications have been reported at this time; patients have demonstrated excellent outcomes in physical exam in postoperative clinic visits. All patients have expressed satisfaction with their results at final visit.